Ultralong Durability of Porous α-Fe2O3 Nanofibers in Practical Li-Ion Configuration with LiMn2O4 Cathode - Jayaraman, Sundaramurthy (2017)
Prelithiated, electrospun α-Fe2O3 nanofibers display an exceptional cycleability when it is paired with commercial LiMn2O4 cathode in full-cell assembly. The performance of such α-Fe2O3 nanofibers is mainly due to the presence of unique morphology with porous structure, appropriate mass balance, and working potential. Also, synthesis technique cannot be ruled out for the performance.